2019
DOI: 10.1210/js.2019-mon-lb009
|View full text |Cite
|
Sign up to set email alerts
|

MON-LB009 Renin Angiotensin Aldosterone System Inactivation in Postural Orthostatic Tachycardia Syndrome

Abstract: Postural Orthostatic Tachycardia Syndrome (POTS) is a clinical syndrome characterized by the presence of tachycardia in the absence of orthostatic hypotension; symptoms of orthostatic intolerance (presyncope and syncope) are present secondary to autonomic dysfunction (1). It is thought that one of the implications for POTS involves plasma volume disturbances leading to blood pooling. The Renin Angiotensin Aldosterone System (RAAS) is one system that assists in plasma volume regulation (2). In this study we hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In light of the important role of the RAAS in regulating human neurohormones of plasma volume, a perturbed RAAS axis, which is disabled to facilitate the enlargement of blood volume in response to the hypovolemia of POTS patients, might be one of the pathophysiological changes in POTS ( 34 ). Several studies have found an inappropriately low plasma renin activity (PRA) in some children and adolescents with POTS, despite the hypovolemia ( 21 , 24 , 35 ), reduced aldosterone levels, and elevated angiotensin (Ang) II levels, with an insensitive receptor response to Ang II ( 35 ).…”
Section: Perspectives On the Pathogenesis Of Potsmentioning
confidence: 99%
“…In light of the important role of the RAAS in regulating human neurohormones of plasma volume, a perturbed RAAS axis, which is disabled to facilitate the enlargement of blood volume in response to the hypovolemia of POTS patients, might be one of the pathophysiological changes in POTS ( 34 ). Several studies have found an inappropriately low plasma renin activity (PRA) in some children and adolescents with POTS, despite the hypovolemia ( 21 , 24 , 35 ), reduced aldosterone levels, and elevated angiotensin (Ang) II levels, with an insensitive receptor response to Ang II ( 35 ).…”
Section: Perspectives On the Pathogenesis Of Potsmentioning
confidence: 99%